2006
DOI: 10.1002/path.2021
|View full text |Cite
|
Sign up to set email alerts
|

Array CGH profiling of favourable histology Wilms tumours reveals novel gains and losses associated with relapse

Abstract: Despite the excellent survival of Wilms tumour patients treated with multimodality therapy, approximately 15% will suffer from tumour relapse, where response rates are markedly reduced. We have carried out microarray-based comparative genomic hybridisation on a series of 76 Wilms tumour samples, enriched for cases which recurred, to identify changes in DNA copy number associated with clinical outcome. Using 1Mb-spaced genome-wide BAC arrays, the most significantly different genomic changes between favourable h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
122
2
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(142 citation statements)
references
References 42 publications
15
122
2
2
Order By: Relevance
“…In Wilms tumors, 1q gain was described to be a predominant alteration in comparative genomic hybridization analyses (Hing et al, 2001). Interestingly, LOH at loci 1q21-22 and 1q32 has been also associated with tumor adverse outcome (Law et al, 1997;Natrajan et al, 2006). Our LOH findings are consistent with these previous reports and indicate that the HRPT2 locus HRPT2 loss and mutation in renal tumors J Zhao et al might be one of critical targets contributing to the development of these renal tumors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In Wilms tumors, 1q gain was described to be a predominant alteration in comparative genomic hybridization analyses (Hing et al, 2001). Interestingly, LOH at loci 1q21-22 and 1q32 has been also associated with tumor adverse outcome (Law et al, 1997;Natrajan et al, 2006). Our LOH findings are consistent with these previous reports and indicate that the HRPT2 locus HRPT2 loss and mutation in renal tumors J Zhao et al might be one of critical targets contributing to the development of these renal tumors.…”
Section: Discussionsupporting
confidence: 89%
“…No specific gene mutation has yet been identified as a direct contributor to their pathogenesis. Wilms tumor is known to have allelic loss at numerous loci (Grundy et al, , 1998Law et al, 1997;Klamt et al, 1998;Natrajan et al, 2006). One Wilms tumor gene (WT1) has been identified and mapped to 11p13 (Call et al, 1990;Gessler et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial artificial chromosome clones were spotted in triplicate onto Corning GAPSII-coated glass slides (Corning, NY, USA). Labelling of 250 ng of non-amplified DNA obtained from microdissected frozen sections or 1000 ng of DNA retrieved from microdissected formalin-fixed paraffin-embedded tissue sections, hybridisation and washes were carried out essentially as described previously (Reis-Filho et al, 2005b, 2006aNatrajan et al, 2006).…”
Section: Microarray-based Comparative Genomic Hybridisationmentioning
confidence: 99%
“…Approximately 15-20% of cases of Wilms tumour relapse, more frequently within the first 2-5 years following the primary diagnosis; in these cases, the risk of recurrence is mainly related to the morphological and molecular features of the previous tumour [12,8,18,7,14].…”
Section: Discussionmentioning
confidence: 99%
“…The association of chemotherapy and radiotherapy to radical nephrectomy has increased the overall survival rate up to 85-90% [3,6];however, in spite of these therapeutic improvements, tumour relapses in a subset of patients (15-20%) [12].Numerous studies have demonstrated that the risk of recurrence can be associated to different features such as histological tumour pattern and loss of heterozygosis (LOH) at 1p and/or 16q, as well as gain of chromosome 1 and other recently described alterations [8,18,7,14]. The recurrence risk is greater within the first 2 years after primary diagnosis (in these patients the percentage of survival approximaly ranges from 24% to 43%) but late relapses have occasionally been reported [1,10].…”
Section: Introductionmentioning
confidence: 99%